Keraton Yogyakarta Masa Lampau dan Masa Kini: Dinamika Suksesi Raja-Raja Jawa dan Politik Wacana “Raja Perempuan” - Ilmiawati Safitri (Indonesian Historical Studies, 2019)
This article presents the dynamics of the succession of the king's regime in the Yogyakarta palace, which entered the crisis period because of the absence of successors to the male king. The emergence of the queen discourse that echoed at the Yogyakarta palace since 2010. It has sparked new tensions for the relatives of the palace. This discussion continues to grow. The words of the king echoed by Sultan Hamengku Buwono X under the pretext of gender became political ambition to perpetuate power. This study used the historical method to answer the problems that in every change of regimes in the Sultan Palace, Yogyakarta was always followed by conflicts over the throne and tug of war which affected the people outside the palace, such as when Islamic Mataram broke into four kingdoms. At that time, the community took part in regional warfare. This impact arose because of the desires of every descendant of the king, who feels entitled to become the next king.